Retroperitoneal Teratoma in an Adult: A Potential Pitfall in the Differential Diagnosis of Adrenal Myelolipoma - Madoka Kataoka; Hiroshi Fukushima; Yasukazu Nakanishi; Minato Yokoyama; Nobuaki Funata; Toru Motoi; Ken-ichi Tobisu; Fumitaka Koga (Case Reports in Urology)
We report a 32-year-old female case of a right adrenal gland mass detected on CT scan at medical checkup. CT and MRI showed a mass of 5.1 cm made of fat and calcification in the right adrenal gland, leading to the clinical diagnosis of adrenal myelolipoma. Because of its relatively large size and the patient’s desire, the patient underwent gasless single-port retroperitoneoscopic adrenalectomy using the RoboSurgeon system. Histopathological examination revealed that the cystic tumor is composed of keratinized epidermis, mature fat, nerve, cartilage, bone, and sebaceous glands compressing the normal adrenal gland, leading to the diagnosis of retroperitoneal mature cystic teratoma. The patient remains free of recurrence 29 months after surgery. Retroperitoneal teratoma is relatively rare but clinically important because of high possibility of malignancy. In a case of an adrenal mass difficult to clinically distinguish retroperitoneal teratoma from adrenal myelolipoma, surgical resection via a minimally invasive approach would be the best therapeutic option.